2011
DOI: 10.1016/j.funeco.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes as potential pathogens of the baobab species Adansonia gregorii: a focus on the Botryosphaeriaceae

Abstract: Adansonia gregorii (baobab) is an iconic tree species occurring in the NW of Australia. Dying baobabs, A. digitata, have been reported from southern Africa and as A. gregorii is closely related to A. digitata, surveys were conducted to assess the health of the Australian baobab. The endophytic microflora of A. gregorii and surrounding tree species was sampled and the ability of these endophytes to cause disease in A. gregorii was determined. Endophytes were isolated from asymptomatic baobabs across 24 sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
60
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 48 publications
4
60
0
7
Order By: Relevance
“…For example, C. africana had the most diverse assemblage of these fungi while S. lancea had the lowest level of diversity. These results are similar to the study of Sakalidis et al (2011a) where 11 Botryosphaeriaceae species were found on both Adansonia gregorii and native surrounding trees at three sites in Australia. In that study, each host showed a different Botryosphaeriaceae species diversity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For example, C. africana had the most diverse assemblage of these fungi while S. lancea had the lowest level of diversity. These results are similar to the study of Sakalidis et al (2011a) where 11 Botryosphaeriaceae species were found on both Adansonia gregorii and native surrounding trees at three sites in Australia. In that study, each host showed a different Botryosphaeriaceae species diversity.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, S. viticola was isolated from three different families of trees Fabaceae, Cannabaceae and Celastraceae but not from the Anacardiaceae. Although some previous studies have considered larger numbers of potential host plants and were conducted over larger areas (Sakalidis et al 2011a;Taylor et al 2009), patterns of host association were not clear. For example, Sakalidis et al (2011a) showed that at one site, Pseudofusicoccum kimberleyense overlapped on hosts residing in three families (Fabaceae, Myrtaceae and Moraceae), but similar levels of overlap were not observed at other sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR and sequencing reactions were purified either by sodium acetate and ethanol precipitation 190 (Zeugin and Hartley 1985) or using sephadex, as described previously (Sakalidis et al 2011). PCR 191 amplicons were sequenced in both directions using the T7 and SP6 primers.…”
mentioning
confidence: 99%